MOLECULAR MECHANISMS OF METFORMIN ACTION: FROM METABOLIC EFFECTS TO LIFESPAN EXTENSION AND HEALTHSPAN PROMOTION: Metformin’s Molecular Effects on Aging and Healthspan - Vujovic, Slavica; Perovic, Svetlana; Vlaovic, Milorad; Scepanovic, Stasa; Filipovic, Aleksandra (Journal of Medical Biochemistry, 2025)
Background : Metformin, a biguanide primarily used for the treatment of type 2 diabetes mellitus, has attracted significant attention for its potential anti-aging effects. As aging becomes the primary risk factor for chronic diseases, interventions targeting fundamental aging processes are gaining traction in biomedical research. Mechanisms of Action: Accumulating evidence suggests that metformin exerts geroprotective effects through multiple interconnected pathways. These include activation of AMP-activated protein kinase (AMPK), inhibition of the mechanistic target of rapamycin (mTOR), attenuation of oxidative stress, modulation of mitochondrial biogenesis, and reduction of low-grade systemic inflammation. Together, these actions address key hallmarks of aging such as cellular senescence, dysregulated nutrient sensing, and altered proteostasis. Preclinical and Clinical Evidence: Animal studies have consistently shown that metformin extends both lifespan and healthspan. In humans, retrospective epidemiological data indicate reduced incidence of cancer, cardiovascular disease, and cognitive decline among metformin users. The TAME (Targeting Aging with Metformin) trial represents the first large-scale attempt to formally assess aging-related outcomes in a non-diabetic population. Challenges and Perspectives: Despite promising data, uncertainties remain regarding optimal dosing, long-term safety, and applicability in healthy aging populations. Furthermore, individual variability in response to metformin suggests the need for precision medicine approaches. Conclusion: Metformin stands at the intersection of metabolic regulation and aging biology. While not a panacea, its favorable safety profile and multi-targeted actions make it a leading candidate for repurposing as an anti-aging therapy. Continued clinical validation is essential to translate these insights into practice.